Polymorphisms but Not Mutations of the KCNQ1 Gene Are Associated with Lone Atrial Fibrillation in the Chinese Han Population - Hui-min Chu; Ming-jun Feng; Yi-gang Li; Yi-xin Zhang; Ji-fang Ma; Bin He; Yi-bo Yu; Jing Liu; Xiao-min Chen (The Scientific World Journal)
Background. Recent studies suggest that mutation of the slow delayed rectifier potassium channel (IKs) contributes to familial atrial fibrillation (FAF). In the current study, we identified common genetic variants of KCNQ1 and explored the potential association between KCNQ1 polymorphism with lone AF (LAF). Methods. Clinical data and blood samples were collected from 190 Han Chinese patients with sporadic AF and matched healthy controls. Variants of the KCNQ1 gene were identified using single-strand conformational polymorphism (SSCP) analysis. A case-control association study in KCNQ1 identified six known single-nucleotide polymorphisms (SNPs) during SSCP screening of the 190 LAF patients and 190 healthy controls. Results. One of the SNPs in KCNQ1 was strongly associated with LAF; significant allelic association was detected rs59233444 (P=0.013, OR=1.469, 95% confidence interval (CI): 1.083–1.993). A multiple regression analysis indicated that rs59233444 is an independent risk factor for LAF. Twelve new variants were identified in KCNQ1, including one in the 5′-UTR, two in the 3′-UTR, six in introns, two synonymous substitutions, and one missense substitution. Variants c.1009C>T, c.1860C>T, and c.+2285C>T were not present in the 190 controls, and the others were identified in controls at various frequencies. Conclusions. rs59233444, a common SNP but not mutation in the coding regions of the KCNQ1 gene, is a risk factor for LAF in Chinese Han population.